The Influence of an Agricultural Subsidy Extension Program on Smallholder Maize Farmers in Tanzania - Christopher Lameck; Kizito Mwajombe; Scott D. Scheer (Journal of International Agricultural and Extension Education, 2019)
Smallholder farming in Tanzania is a household activity implemented at the subsistence level. The government of Tanzania launched the subsidy program to promote food secure households and shift subsistence farming to business farming. Food insecurity was associated by low rates of fertilizer application and poor seed quality among smallholder farmers due to fertilizer and seed costs which led to an increase in food prices. This study aimed at assessing the impact of the agricultural subsidy program for smallholder maize farmers. Four research objectives focused on agricultural productivity, food security, usage of improved inputs, and farmers’ perceptions of how the program functioned. An ex post facto research design was used with a sample of 120 smallholder farmers. The investigation involved 60 farmers who received subsidies and 60 who did not. The study used an interviewer administered questionnaire. Farmers who received subsidies significantly increased maize production. Comparison of average output before and after subsides shows an increase in number of bags (100 kg) per acre from an average of 5.35 bags to 10.10 bags. Farmers who did not receive subsides produced about the same amount of maize at time one and time two. There was general satisfaction with the functioning of the program, however certain areas need to be improved including that program objectives are followed, ensuring farmers can manage market price of inputs, and enhancing extension services for farmers to produce more surplus.
Keywords: smallholder farmers; maize; Tanzania; extension subsidy program